EVALUATION OF CLEAN WATER SUPPLY SYSTEMS OF DARUL HIKMAH MOSQUE IN POLITEKNIK NEGERI SEMARANG - Santosa, Stefanus; Suhartono, Edy; Fahdiyat, Lukman; Pertiwi, Zulaikha Putri (Politeknik Negeri Semarang, 2020)
Darul Hikmah Mosque is a building located inside Politeknik Negeri Semarang as a place of worship for all campus residents, and people who live around the area. The prayer activity is preceded by the Wudu. In order for Wudu to be carried out perfectly, sufficient quantities of water are needed. The lack of pressure and discharge of Wudu tap water, when used simultaneously, becomes a constraint that is the water pressure decreases. The purpose of this study is to determine the factors causing the lack of water discharge or pressure as required in SNI 03-7065-2005. The research method is quantitative descriptive by evaluating the performance of the existing water supply system and using a discrepancy model by comparing the evaluation results with existing data to find discrepancies. Evaluation results indicate that the factors that cause the lack of water pressure are the roof tank height is less than ideal for water distribution with gravitational power, and the volume of available water is not sufficient